Dibenzobarrelene‐Based Azaacenes: Emitters in Organic Light‐Emitting Diodes. Issue 18 (3rd March 2017) - Ganschow, Michael; Koser, Silke; Hahn, Sebastian; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: The synthesis of soluble dibenzobarrelene‐substituted azaacenes either by condensation reactions in solution or, more effectively, in the solid state by using a ball mill is reported herein. We relate their optical properties in thin films to their packing in the solid state. The targets are characterized by cyclic voltammetry, X‐ray crystallography and UV/Vis and fluorescence analysis. Three highly fluorescent, amorphous azaacenes were processed into organic light‐emitting diodes, and their improved performance (luminance, efficiency and efficacy) was compared with that of structurally related iptycene‐based azaacenes. Abstract : Milled to perfection : Direct fusion of dibenzobarrelene moieties to azacenes cores (see figure), either through classic condensation reactions or by solvent‐free ball‐milling, leads to soluble solid‐state emitters that exhibit improved performance with respect to their iptycene analogues.